2017
DOI: 10.1002/rob.21770
|View full text |Cite
|
Sign up to set email alerts
|

Description and experimental results of a panoramic K‐band radar dedicated to perception in mobile robotics applications

Abstract: Description and experimental results of a panoramic K-Band radar dedicated to perception in mobile robotics applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…After these processing, the range, velocity and angle information of objects are obtained. In addition to these above issues, some other problems need to be considered, such as, the pre-processing of the raw ADC data, the constant false alarm rate (CFAR) 38,39 , and so on. However, these topics are out of scope of this paper and not discussed.…”
Section: Radar Detection Principlementioning
confidence: 99%
“…After these processing, the range, velocity and angle information of objects are obtained. In addition to these above issues, some other problems need to be considered, such as, the pre-processing of the raw ADC data, the constant false alarm rate (CFAR) 38,39 , and so on. However, these topics are out of scope of this paper and not discussed.…”
Section: Radar Detection Principlementioning
confidence: 99%
“…it is suitable for distinguishing between stationary and moving objects, and can be used to discard moving objects during the map-building process [62]. Some research on using Radar for SLAM can be found in [42,[62][63][64][65][66]. When compared to Lidar, lower price, lower power consumption, and less sensitivity to atmospheric conditions make it well suited for outdoor applications.…”
Section: Sensors and Fusion Methods For Slammentioning
confidence: 99%
“…In addition to MIMO, the AoA can also be measured by a spinning directive antenna, for each moment the radar outputs an 1D power–range spectrum for the inspected line of sight, where the azimuth angle is the radar’s own azimuth angle relative to the fixed coordinate [ 115 ]. In [ 117 , 118 ], a designated spinning radar device called PELICAN was constructed and evaluated for mobile robotics applications.…”
Section: Sensors and Sensor-based Odometry Methodsmentioning
confidence: 99%